2015
DOI: 10.1016/j.aop.2015.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non-uniform exchange field in ferromagnetic graphene

Abstract: We have presented here the consequences of the non-uniform exchange field on the spin transport issues in spin chiral configuration of ferromagnetic graphene. Taking resort to the spin orbit coupling (SOC) term and non-uniform exchange coupling term we are successful to express the expression of Hall conductivity in terms of the exchange field and SOC parameters through the Kubo formula approach. However, for a specific configuration of the exchange parameter we have evaluated the Berry curvature of the system… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This expression of Berry curvature shows that it is the source of monopole, if they exist. Further, it can be shown that in ferromagnetic graphene, if the spin orbit interaction is taken into account along with the inhomogeneous exchange vector, the Berry curvature is the origin of the spin orbit torque [8].…”
Section: Analysis With Space Dependent Exchange Couplingmentioning
confidence: 99%
“…This expression of Berry curvature shows that it is the source of monopole, if they exist. Further, it can be shown that in ferromagnetic graphene, if the spin orbit interaction is taken into account along with the inhomogeneous exchange vector, the Berry curvature is the origin of the spin orbit torque [8].…”
Section: Analysis With Space Dependent Exchange Couplingmentioning
confidence: 99%